(untitled) (Indian Journal of Animal Production and Management, 2013)
A study was carried out to investigate the influence of buck effect and PGF2á treatment on frequency of oestrus behavioural pattern in indigenous goats. A total of 16 nulliparous goats with a mean age and body weight of 15.38±0.96 months and 13.63±0.58 kg respectively were divided into three groups. The 1st group (control, n=4) was kept separate without any treatment, the 2nd group (T1, n=6) was treated with 2 injections of PGF2á at 11 days apart @ 7.5mg/animal/ injection while the third group (T2, n=6) was teased with a sexually active buck. Teasing was done by keeping a buck permanently with does till all the does came into oestrus. The buck was approned to prevent unknown mating. Heat detection was carried out for half an hour at every six hours interval using a teaser buck. There was no significant difference (P>0.05) in frequency of oestrus behavioural activities among the groups. Overall, the maximum frequency of behavioural activities was tail fanning (87.5%) followed by bleating (75%), buck clustering and buck teasing (43.75% each), frequent micturition (37.5%) and male seeking (31.25%). While the oestrus behaviour observed with least frequency were mounting and mounted by others (12.5% each). Although there was no significant difference in frequency of behaviour between the groups, there was higher frequency observed in T2 group especially for bleating and tail fanning. It was found that the buck effect and PGF2á treatment do not have much influence on frequency of oestrus behavioural pattern in indigenous goats.